Mitos Larangan sebagai Kearifan Lokal Masyarakat Jawa di Banyuwangi (Kajian Etnolinguistik) - Ma’arif, Moh. Syamsul; Kurniawan, Heru (Indo-MathEdu Intellectuals Journal, 2024)
The myth of prohibition in Javanese society, especially Tegaldlimo District, has an important role in regulating behavior, maintaining cultural values, and maintaining cosmic balance. This research identifies various prohibition myths in Tegaldlimo District using qualitative field methods. Data collection techniques involve observation, interviews, and documentation. The data analysis technique for this research uses Sugiono's theory, namely data reduction, data presentation, and drawing conclusions. The results of this research show 15 data findings on the form and meaning of prohibition myth expressions. As well as the function of myths in socio-cultural life, namely: Regulating social behavior, strengthening cultural identity, maintaining cosmic balance, legitimizing power and position, teaching and education, forecasting and prediction, maintaining ritual and ceremonial traditions, understanding cosmology and mythology, solving social problems and conflict, building solidarity and togetherness, inspiring art and creativity, healing and health, managing natural resources, social reproduction and generation, cultural reflection and evaluation.